(untitled) (TAMADDUN NURI JURNALI, 2025)
The article examines the symbolic images used in dastan stories, analyzes key symbols such as the image of a hero, horse, sword, sacred tree and other elements that carry sacred and cultural meaning. Particular attention is paid to their function in constructing a narrative, their connection with folk beliefs, mythology and historical realities of Khorezm.